A study of contemporary Ghana : some aspects of social structure Volume Two - Birmingham, Walter Barr.; Neustadt, I.; Omaboe, E. N. (London : Published for the Ghana Academy of Sciences by Allen & Unwin, 1967)
The study is meant to describe a series of aspects of contemporary Ghanaian Society and, above all bring together in a handy and systematic form some of the scattered and unanalyzed but available material on Ghana as a whole. In the event, the section on the economy of Ghana became a substantial volume in itself whose contributors were able to incorporate a good deal of original research material in the analysis of available sources. It is hoped that the book will serve as a work of reference for public servants, university staff and students, teachers in training colleges, and in the senior years of secondary schools.
Includes index.
aia 11/04/2017
Loans
Keywords: Social conditions; Economic istory; Politics and government; Ghana